Active Learning Versi Rasulullah dan Implementasinya dalam Pembelajaran PAI - Uyung Yuliza; Sunhaji Sunhaji; Wahab Wahab (Jurnal Kependidikan)
Facts in the world of education, especially about learning methods, it is said that the western world is more advanced than the Islamic world. It is undeniable that Islam contains a source of inspiration for the development and progress of science, including the field of education. Starting from this thought, this paper intends to provide input to the Islamic education environment by seeking to explore and present the learning methods used by the Prophet in his da'wah. Many hadiths about the way the Prophet educated his friends contain elements of an active learning strategy. By studying the hadith of the Prophet, various learning strategies will be found that can be used as a reference for developing current learning methods. This paper aims to describe the hadith of the Prophet as a source of active, creative and innovative learning methods that he has ever done by suggesting several hadiths as considerations to be implemented in active learning in Islamic Religious Education subjects.